Multicentric reticulohistiocytosis: A clinicoradiological review - Anindita Sinha; Santosh Dhungana; Dipankar De; Mahesh Prakash; Shefali Khanna Sharma; Ashim Das (Indian Journal of Rheumatology)
Multicentric reticulohistiocytosis is a rare systemic disease described as a lipoid dermato-arthritis. Characteristic involvement includes multiple skin nodules and progressive arthritis. Involvement of skin, mucosa, and internal organs has been described. Predominant involvement of the distal interphalangeal joint occurs in the hands. Other joints involved are knee, shoulder, and hips. Rarely, vertebral involvement may also occur. A significant association with underlying solid organ as well as hematologic malignancies warrants a thorough workup and imaging screening. Diagnosis is based on histopathologic findings of histiocytic infiltration with multinucleated giant cells. Radiographic manifestations in the multiple joints are characterized by symmetrical destructive and erosive arthritis. Ultrasound of the hands may be helpful in detecting the nodules in characteristic periarticular distribution in early presentations. We describe the common and uncommon clinical and imaging features of early and late manifestations of the disease.